Fe/Indonesian Natural Zeolite as Hydrodeoxygenation Catalyst in Green Diesel Production from Palm Oil - Riandy Putra; Witri Wahyu Lestari; Fajar Rakhman Wibowo; Bambang Heru Susanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
The Petroleum diesel-based fossil fuel remains the primary source of energy consumption in Indonesia. The utilization of this unrenewable fuel depletes fossil fuels; thus, an alternative, renewable fuel, such as one based on biohydrocarbon from biomass-green diesel-could be an option. In this work, green diesel was produced through the hydrodeoxygenation from palm oil and processed in a batch-stirred autoclave reactor over natural zeolite (NZ) and NZ modified with 3 wt.% Fe metal (Fe/NZ) as heterogeneous catalyst. NZ showed high crystallinity and suitability to the simulated pattern of the mordenite and clinoptilolite phases according to X-ray diffraction (XRD) analysis. The presence of Fe metal was further confirmed by XRD, with an additional small diffraction peak of Fe0 that appeared at 2θ = 44-45°. Meanwhile, NZ and Fe/NZ were also characterized by Scanning electron microscopy (SEM) with Energy Dispersive X-ray (EDX), X-ray Fluorescence (XRF), and Surface Area Analyzer (SAA). The obtained materials were tested for the conversion of palm oil into diesel-range hydrocarbons (C15-C18) under conditions of 375 °C and 12 bar H2 for 2 h. NZ and Fe/NZ produced a liquid hydrocarbon with straight-chain (C15-C18) alkanes as the most abundant products. Based on Gas Chromatography-Mass Spectrometry (GC-MS) measurement, a higher conversion of palm oil into diesel-like hydrocarbons reached more than 58% and 89%, when NZ and Fe modified NZ (Fe/NZ), respectively were used as catalysts.